The Feasibility of Audio-Visual Based Digital Storytelling on the YouTube Channel of Our Fairy Tales as a Learning Media - Nancy Angelia Purba; Restio Sidebang; Kresna Ningsih Manik; Surinah (Jurnal Sastra Indonesia, 2026)
The development of digital technology has encouraged the use of audiovisual learning media in literary learning in higher education. However, conventional methods still dominate literary learning, so more innovative and interesting media for students are needed. This study aims to analyze the feasibility of audio-visual-based digital storytelling on the "Dongeng Kita" YouTube channel as a literary learning medium for students of the Elementary School Teacher Education Study Program (PGSD). The research uses a qualitative, descriptive approach. Data were obtained through listening, recording, and documentation techniques for five video stories, selected purposively from a total of 723 videos on the "Dongeng Kita" channel. Data analysis was conducted using a pragmatic and pedagogical content analysis, focusing on content, presentation, language, and technical aspects. The study found that digital storytelling on the "Dongeng Kita" channel received an average score of 4.54, placing it in a very decent category. The content aspect obtained a score of 4.6, presentation 4.5, language 4.6, and technical 4.6. Digital storytelling is believed to increase students' understanding, motivation, and involvement in literary learning. This research contributes an audio-visual-based digital storytelling evaluation model that can serve as a reference for the development of technology-based literary learning media in universities.